The effect of attitude and subjective norm on intention to use and behavior to use QRIS with moderation of digital literacy of UNS students - Aulia Nur Arfani; Khresna Bayu Sangka (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study investigates the influence of attitude and subjective norm on the intention to use and actual usage behaviour of QRIS, with digital literacy serving as a moderating variable among students at Sebelas Maret University. Grounded in behavioural intention and technology adoption perspectives, the research seeks to understand the factors shaping students’ adoption of digital payment systems within the rapidly expanding cashless economy in Indonesia. Employing a quantitative descriptive research design, primary data were collected through structured questionnaires distributed via Google Forms using a four-point Likert scale. The study involved 385 active university students from the 2025/2026 academic year who had prior experience using QRIS. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS. The findings demonstrate that attitude exerts a positive and significant influence on students’ intention to use QRIS, indicating that favourable perceptions toward digital payment systems increase adoption intention. Subjective norm was also found to positively and significantly influence intention to use, suggesting that social influence and peer recommendations play an important role in shaping technology adoption behaviour among students. Furthermore, intention to use significantly affects actual QRIS usage behaviour, confirming the importance of behavioural intention as a predictor of digital payment utilisation. The study also reveals that digital literacy significantly strengthens the relationship between intention to use and actual usage behaviour, highlighting the critical role of digital competencies in facilitating effective adoption of financial technology services. These findings contribute to the growing literature on digital payment adoption, financial technology behaviour, and digital literacy within higher education contexts in emerging economies. Keywords: Attitude; Subjective Norm; Intention to Use; Behavior to Use; Theory of Reasoned Action (TRA); Digital Literacy ; QRIS